A Simple and Cost-effective Technique for Vertebroplasty. Issue 1 (March 2015) - Bharti, Ajay; Swaroop, Anand; Kumar, Pramod; Rawat, Ashok
Abstract : Multiple instrumentations are available by which fairly good transpedicular vertebroplasty can be performed. Usually needle/cannula are used for vertebroplasty and percutaneous injection of Acrylic cement is injected in the symptomatic vertebrae. Important attributes include the shape of the tip of the stylet and the cannula and the ease to use it, as well as the type of bone cement used. The authors present a simple technique for vertebroplasty that utilizes high viscosity bone cement at low temperature with a simplified cannula system consisting of Steinmann pin and a drill sleeve with 5-mL disposable syringe, which also incurs very low cost.